A diaphragm and its use
Patent Information
- Application Number
- CN202510483495.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-16
- Publication Date
- 2026-10-23
AI Technical Summary
通过在高分子基膜上涂覆陶瓷层和涂胶层用于改善耐热性和粘接性,但通常遇到粘接力不足、满充界面褶皱改善效果不佳以及长循环性能不足等问题,增加涂胶层改善粘结力时,发现界面褶皱的问题并不会因为涂胶层胶量的增加而有所改善,反而会存在涂胶量增加,容易发生堵孔的问题,导致隔膜整体阻抗增加,影响电芯的动力学性能
[0018]综上所述,本发明提出一种隔膜及其应用,能够提高耐热层和多孔基膜的界面相容性,改善隔膜阻抗,能够获得表面平滑的耐热层,从而提高耐热层与其上聚合物层的实际接触面积,使得隔膜整体的粘接能力提高,改善电芯界面褶皱问题,从而提高电池的循环性能。能够提高形成的聚合物层的均匀性,获得均匀涂覆的聚合物层。能够提高隔膜的机械性能,同时兼顾柔韧性,提高隔膜的离子传输性能,减少与电解液的接触面积,提高隔膜的化学稳定性。能够提高隔膜的耐高温性能,改善多孔基膜高温下的热收缩,且确保锂离子的顺利传导。通过低涂覆量且具有较高聚合物层覆盖率,获得的隔膜的粘结力提高,且改善界面褶皱问题,降低隔膜阻抗,改善电池的长循环性能。
Smart Images

Figure BDA0005363787900000181
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, and more specifically to a separator and its application. Background Technology
[0002] In today's pursuit of green development, lithium-ion batteries play a crucial role. They possess advantages such as high operating voltage, high energy density, long cycle life, low self-discharge, and no memory effect, making them widely used in digital products, electric vehicles, and energy storage. However, as the penetration rate of power batteries gradually increases, their energy density and safety face significant challenges, necessitating further reform and innovation in lithium-ion battery raw materials.
[0003] The separator is one of the key raw materials in lithium-ion batteries. Its main function is to isolate the positive and negative electrodes, prevent short circuits, and allow lithium-ion transport. With the increasing demands for energy density and safety performance in lithium-ion batteries, separator materials are required to be further thinned and have improved heat resistance while also maintaining adhesion. Coating a ceramic layer and an adhesive layer onto a polymer base film can improve heat resistance and adhesion, but this often encounters problems such as insufficient adhesion, poor improvement in full-charge interface wrinkles, and insufficient long-cycle performance. Increasing the amount of adhesive to improve adhesion reveals that the interface wrinkles are not improved by increasing the amount of adhesive; in fact, increased adhesive can lead to pore blockage, resulting in increased overall separator impedance and affecting the cell's dynamic performance. Summary of the Invention
[0004] This invention proposes a separator and its application. The separator with low coating amount and high polymer layer coverage proposed in this invention and its application can improve the adhesion of the separator, improve the interface wrinkling problem, reduce the separator impedance, and improve the long cycle performance of the battery.
[0005] To address the aforementioned technical problems, the present invention proposes a diaphragm comprising at least:
[0006] Porous base membrane;
[0007] A heat-resistant layer is disposed on at least one surface of the porous base membrane, the heat-resistant layer comprising fumed alumina and nanocellulose; and
[0008] A polymer layer is disposed on the surface of the porous base membrane away from the heat-resistant layer and / or on the surface of the heat-resistant layer away from the porous base membrane, wherein the coating amount of the polymer layer is 0.3 g / m². 2 -0.7g / m 2 The polymer layer has a coverage of 25%-60%.
[0009] In one embodiment of the present invention, the mass ratio of the fumed alumina to the nanocellulose is 2:8-5:5, and the median particle size of the fumed alumina powder is 50nm-100nm.
[0010] In one embodiment of the present invention, the nanocellulose includes at least one of cellulose nanofibers or nanofiber crystals, and the diameter of the nanocellulose is less than or equal to 100 nm, and the length of the nanocellulose is less than or equal to 100 μm.
[0011] In one embodiment of the present invention, the heat-resistant layer further includes a first dispersant and a first binder, wherein the first dispersant is selected from acrylic dispersants and the first binder is selected from acrylate binders.
[0012] In one embodiment of the present invention, the thickness of the heat-resistant layer is 0.2 μm-0.9 μm, and the bulk density of the heat-resistant layer is 0.5 g / cm³. 3 -1.2g / cm 3 The diaphragm has a heat shrinkage rate of less than 1% after being baked at 150°C for 1 hour.
[0013] In one embodiment of the present invention, the polymer layer comprises a second dispersant and a second binder, wherein the mass ratio of the second dispersant to the material density of the second binder per square meter of the polymer layer is 0.002-0.005:1, and the material density of the second binder is 0.6 g / cm³. 3 -1.2g / cm 3 .
[0014] In one embodiment of the present invention, the second binder comprises at least one of polymethyl methacrylate and its copolymers or polyacrylate and its copolymers; the second dispersant comprises octadecyl methacrylate.
[0015] In one embodiment of the present invention, the polymer layer further includes a third adhesive, the third adhesive comprising at least one of polyacrylate and its copolymers, polyacrylonitrile or acrylic polymer, and the molecular weight of the third adhesive being greater than 300,000.
[0016] In one embodiment of the present invention, in the polymer layer, the mass ratio of the second binder to the second dispersant is 75-400:1, the mass ratio of the second binder to the third binder is 8-15:1, the median particle size of the second binder is 5μm-10μm, and the median particle size of the third binder is less than 1μm.
[0017] The present invention also provides a lithium-ion battery comprising the separator described above.
[0018] In summary, this invention proposes a separator and its application, which can improve the interfacial compatibility between the heat-resistant layer and the porous base film, improve separator impedance, obtain a smooth heat-resistant layer, thereby increasing the actual contact area between the heat-resistant layer and the polymer layer on it, improving the overall adhesion of the separator, improving the cell interface wrinkling problem, and thus improving the battery cycle performance. It can improve the uniformity of the formed polymer layer, obtaining a uniformly coated polymer layer. It can improve the mechanical properties of the separator while maintaining flexibility, improve the ion transport performance of the separator, reduce the contact area with the electrolyte, and improve the chemical stability of the separator. It can improve the high-temperature resistance of the separator, improve the thermal shrinkage of the porous base film at high temperatures, and ensure smooth lithium-ion conduction. By using a low coating amount and achieving a high polymer layer coverage, the resulting separator has improved adhesion, improved interface wrinkling problem, reduced separator impedance, and improved long-cycle performance of the battery. Detailed Implementation
[0019] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention.
[0020] It should be understood that the invention can be embodied in various forms and should not be construed as being limited to the embodiments set forth herein. Rather, providing these embodiments will make the disclosure thorough and complete, and will fully convey the scope of the invention to those skilled in the art.
[0021] The technical solution of the present invention will be further described in detail below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0022] This invention provides a membrane comprising a porous base membrane, a heat-resistant layer, and a polymer layer, wherein the heat-resistant layer is disposed on at least one surface of the porous base membrane, and the polymer layer is disposed on the surface of the porous base membrane away from the heat-resistant layer and / or on the surface of the heat-resistant layer away from the porous base membrane. The heat-resistant layer comprises fumed alumina (Alu C) and nanocellulose, and the coating amount of the polymer layer is 0.3 g / m³. 2 -0.7g / m 2The polymer layer coverage is 25%-60%. Coating amount refers to the mass of the coating material per unit area of the coated substrate, while coverage refers to the ratio of the area covered by the polymer layer coating material to the observed area of the coated substrate. By adding nanocellulose to improve membrane impedance, the direct current resistance (DCR) of the lithium-ion battery is reduced. Nanocellulose and fumed alumina jointly improve the heat resistance of the membrane. A polymer layer with low coating amount and high coverage improves the membrane's adhesion and reduces interfacial wrinkling, thus improving the battery's long-cycle performance. In this application, the coating amount and coverage of the polymer layer can be adjusted at least by increasing the slurry flow rate, reducing the slurry solids content, adjusting the rotor speed, controlling the mass of the second dispersant, and controlling the material density ratio of the second binder.
[0023] In one embodiment of the present invention, the porous base membrane includes, for example, one or more of polyethylene (PE) membrane, polypropylene (PP) membrane, nonwoven fabric, polyethylene terephthalate (PET) membrane, polyimide (PI) membrane, or polypropylene-polyethylene-polypropylene composite membrane. The thickness of the porous base membrane is, for example, 3 μm-20 μm, and the porosity of the porous base membrane is, for example, 20%-70%. Porosity refers to the percentage of pore volume to the total volume of the material in its natural state in a bulk material.
[0024] In one embodiment of the present invention, the heat-resistant layer further includes a first dispersant and a first binder, wherein the first dispersant is selected from acrylic dispersants, such as at least one of acrylic acid, polyacrylic acid, or polymethacrylic acid, to ensure the uniformity of the heat-resistant slurry dispersion. The first binder is selected from acrylic binders, such as at least one of acrylate, polyacrylate, ethyl polyacrylate, or ethyl polymethacrylate, to improve the adhesion between the heat-resistant layer and the porous base film. The fumed alumina is, for example, in powder form, and the median particle size (Dv) of the fumed alumina powder is... 50 For example, 50nm-100nm, where the median particle size Dv 50 This refers to the diameter of the particle located at 50% of its volume when the particles are arranged in ascending order of diameter. In one embodiment of the present invention, fumed alumina is obtained, for example, by chemical vapor deposition, plasma vapor phase synthesis, sol-gel method, hydrothermal / solvothermal method, or template method, or it can be purchased commercially depending on the range of median particle size of fumed alumina. Fumed alumina can effectively improve the high-temperature resistance of the separator and enhance the safety performance of lithium-ion batteries.
[0025] In one embodiment of the present invention, the nanocellulose (NC) includes, for example, at least one of cellulose nanofibrils (CNF) or cellulose nanocrystals (CNC), and the diameter (D) of the nanocellulose is, for example, less than or equal to 100 nm, and the length L of the nanocellulose is, for example, less than or equal to 100 μm. The nanocellulose is, for example, purchased commercially. In the heat-resistant layer, the nanocellulose, for example, connects to fumed alumina powder particles to form a uniform network structure, covering the porous base membrane, thereby improving the adhesion of the heat-resistant layer. By adding nanocellulose to form a network structure with fumed alumina, the thermal stability and mechanical properties of the lithium-ion battery separator are effectively improved. Simultaneously, the interfacial compatibility between the heat-resistant layer and the porous base membrane is improved, thereby reducing the DC resistance of the lithium-ion battery. Furthermore, by controlling the size of nanocellulose and fumed alumina, a smooth heat-resistant layer can be obtained, thereby increasing the actual contact area between the heat-resistant layer and the polymer layer on it. This improves the overall adhesion of the separator, alleviates the cell interface wrinkling problem, and thus enhances the cycle performance of the battery.
[0026] In one embodiment of the present invention, the content of the first dispersant in the heat-resistant layer is, for example, 0.2wt%-2wt%, the content of the first binder in the heat-resistant layer is, for example, 3wt%-12wt%, and the remainder is fumed alumina and nanocellulose, and the mass ratio of fumed alumina to nanocellulose (denoted as w1 / w2) is, for example, 2:8-5:5. By controlling the content of each substance in the heat-resistant layer, the heat resistance of the obtained membrane can be ensured, and the adhesion between the heat-resistant layer and the porous base membrane can be improved, thereby improving the interfacial compatibility between the heat-resistant layer and the porous base membrane.
[0027] In one embodiment of the present invention, the thickness of the heat-resistant layer is, for example, 0.2 μm-0.9 μm, and the bulk density of the heat-resistant layer is, for example, 0.5 g / cm³. 3 -1.2g / cm 3 The bulk density is defined as the mass per unit volume of the heat-resistant layer, and it is calculated by dividing the heat-resistant layer density by the heat-resistant layer thickness, with units of g / cm³. 3 The density of the heat-resistant layer refers to the weight per unit area of the heat-resistant layer. It is calculated by dividing the weight of the heat-resistant layer by its area, and the unit is g / cm³. 2The membrane exhibits a thermal shrinkage rate of less than 1% after baking at 150°C for 1 hour, and its impedance is ≤0.4Ω lower than that of conventional membranes. In other words, the impedance of the membrane obtained in this application is lower than that of conventional membranes. Conventional membranes include a porous base membrane, a ceramic layer, and an adhesive layer. The difference between the ceramic layer and the heat-resistant layer in this application is that the ceramic layer does not include fumed alumina and nanocellulose; instead, ceramic particles are used to replace fumed alumina and nanocellulose. Examples of ceramic particles include silicon dioxide and alumina. The adhesive layer does not include the second and third binders; instead, polyvinylidene fluoride (PVDF) is used to replace the second and third binders. The rest can be the same as the membrane in this application. The thermal shrinkage rate of the membrane refers to the percentage change in size of the membrane after heating. By controlling the thickness and packing density of the heat-resistant layer, the high-temperature resistance of the membrane is improved, the thermal shrinkage of the porous base membrane at high temperatures is mitigated, and the smooth conduction of lithium ions is ensured.
[0028] In one embodiment of the present invention, the polymer layer includes a second binder, a third binder, and a second dispersant, etc., wherein the second dispersant includes, for example, stearyl methyl acrylate (SMA) to improve the film-forming properties and toughness of the slurry, and the second binder includes, for example, at least one of poly(methyl methacrylate) (PMMA) and its copolymers or polyacrylate and its copolymers. The material density of the second binder is 0.6 g / cm³. 3 -1.2g / cm 3 The mass ratio of the second dispersant to the material density of the second binder per square meter of polymer layer (denoted as m / ρ) is 0.002-0.005:1. In this application, material density is an inherent property of the material, representing the mass per unit volume. By controlling the mass ratio of the second dispersant to the material density of the second binder, the separator achieves a high polymer layer coverage even with a low coating amount. When the mass ratio of the dispersant to the density of the first binder is low, such as 0.001, the polymer slurry is unevenly dispersed and cannot form a uniform polymer layer. When the mass ratio of the dispersant to the density of the first binder is high, the separator impedance increases, affecting the battery cycle performance.
[0029] In one embodiment of the present invention, the third binder includes, for example, at least one of polyacrylate and its copolymers, polyacrylonitrile, or acrylic polymers. The polyacrylate polymer includes, for example, at least one of polyacrylate copolymers or cross-linked polyacrylates, and the molecular weight of the third binder is, for example, greater than 300,000. In the polymer layer, the mass ratio of the second binder to the second dispersant is, for example, 75-400:1, and the mass ratio of the second binder to the third binder is, for example, 8-15:1. By controlling the ratio of the second binder, the third binder, and the second dispersant, the processing performance can be improved, the uniformity of the slurry dispersion can be enhanced, thereby improving the uniformity of the formed polymer layer and obtaining a uniformly coated polymer layer.
[0030] In one embodiment of the present invention, the median particle size (Dv) of the second binder 50 For example, the median particle size of the second and third binders is 5μm-10μm, and the median particle size of the third binder is less than 1μm. By controlling the median particle size of the second and third binders, the mechanical properties of the membrane can be improved while maintaining flexibility, the ion transport performance of the membrane can be improved, the contact area with the electrolyte can be reduced, and the chemical stability of the membrane can be improved.
[0031] In one embodiment of the present invention, a method for preparing a diaphragm is also provided, specifically comprising: dispersing a first dispersant, fumed alumina, nanocellulose and a first binder in a first solvent in a mass ratio to obtain a heat-resistant slurry; dispersing a second binder, a third binder and a second dispersant in a second solvent in a mass ratio to obtain a polymer slurry; coating the heat-resistant slurry onto at least one surface of a porous base membrane and drying it; coating the polymer slurry onto the surface of the porous base membrane away from the heat-resistant layer and / or the surface of the heat-resistant layer away from the porous base membrane and drying it.
[0032] In one embodiment of the present invention, the first solvent is, for example, water, and the total content of the first dispersant, fumed alumina, nanocellulose, and the first binder in the heat-resistant slurry is, for example, 20wt%-45wt%. The second solvent is, for example, water, and the total content of the second binder, the third binder, and the second dispersant in the polymer slurry is, for example, 5wt%-20wt%. By controlling the solute content in the polymer slurry and the heat-resistant slurry, the packing density of the formed heat-resistant layer and the coating amount of the polymer layer can be controlled, thereby controlling the membrane preparation process.
[0033] In one embodiment of the present invention, the heat-resistant slurry is coated, for example, by microgravure coating or wire rod coating, and then dried to obtain a heat-resistant layer. Then, a polymer slurry is coated onto the surface of the porous base membrane away from the heat-resistant layer and / or the surface of the heat-resistant layer away from the porous base membrane by spin coating or similar methods, and dried to obtain a polymer layer. In this embodiment, the polymer coating amount (Cg) is, for example, 0.3 g / m³. 2-0.7g / m 2 The coverage (Cov%) of the polymer layer is, for example, 25%-60%, and further, when the coating amount of polymer is, for example, 0.4 g / m². 2 The coverage of the polymer layer is, for example, 30%-35%. If the coverage is too low, the overall adhesion of the separator is too low, the effect of hot pressing and bonding of the cell is poor, and interface wrinkles will be formed, thus affecting the cycle performance of the battery. If the coverage is too high, the overall air permeability of the separator is too high, the overall impedance increases, and ultimately affects the cycle performance of the battery.
[0034] This invention also proposes a lithium-ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte. The separator is located between the positive and negative electrodes, and the electrolyte is filled between the positive and negative electrodes and the separator. The separator is selected from the aforementioned types. This invention does not limit the type and shape of the lithium-ion battery. In one embodiment, the lithium-ion battery is, for example, a primary battery or a secondary battery. A secondary battery is, for example, a pouch battery, a prismatic battery, or a cylindrical battery.
[0035] In one embodiment of the present invention, the positive electrode sheet includes a positive current collector and a positive active layer coated on at least one surface of the positive current collector. The positive current collector is, for example, a foil formed by surface treatment of materials such as nickel, titanium, aluminum, silver, stainless steel, or carbon. Besides foil, the positive current collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam, or non-woven fabric. The thickness of the positive current collector is, for example, 8 μm-15 μm. In this embodiment, the positive current collector is, for example, an aluminum foil, and the thickness of the aluminum foil is, for example, 13 μm.
[0036] In one embodiment of the present invention, the positive electrode active layer includes a positive electrode active material, a positive electrode binder, and a conductive agent. The active material is selected from at least one of lithium nickel cobalt manganese oxide (NCM), lithium nickel oxide (LNO), lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), lithium cobalt oxide (LCO), or lithium nickel cobalt aluminum oxide (NCA). The positive electrode binder is selected from one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinylidene fluoride-tetrafluoroethylene-propylene terpolymer (ETFE), ethylene-vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer (TFE-HFP-VDF), or tetrafluoroethylene-hexafluoropropylene copolymer (FEP). The conductive agent is selected from one or more of conductive carbon black (Super P), acetylene black, or Ketjen black. The mass ratio of the positive electrode active material, the conductive agent, and the positive electrode binder in the positive electrode active layer is, for example, (90-97):(1-5):(2-5).
[0037] In one embodiment of the present invention, the positive electrode active material is, for example, LiNi. 0.6 Co 0.2 Mn 0.2 O2, a positive electrode binder such as polyvinylidene fluoride, and a conductive agent such as acetylene black are used. The positive electrode active material, conductive agent, and positive electrode binder are mixed in a mass ratio of 97:1:2. An organic solvent is added, and the mixture is stirred under vacuum until the system is homogeneous to obtain a positive electrode slurry. The organic solvent is, for example, N-methylpyrrolidone (NMP). The positive electrode slurry is uniformly coated onto aluminum foil, then air-dried at room temperature and transferred to an oven for drying. The positive electrode sheet is obtained through cold pressing, edge trimming, cutting, and slitting. This application does not limit the method of preparing the positive electrode sheet; in other embodiments, the positive electrode sheet can also be obtained by any other method of forming a positive electrode sheet.
[0038] In one embodiment of the present invention, the negative electrode sheet includes, for example, a negative electrode current collector and a negative electrode active layer coated at least on one surface of the negative electrode current collector. The negative electrode current collector is selected from, for example, a copper foil current collector, a composite copper foil current collector, a carbon current collector, a foamed copper current collector, or a stainless steel current collector, and the thickness of the negative electrode current collector is, for example, 8 μm-15 μm. In this embodiment, the negative electrode current collector is, for example, copper foil, and the thickness of the copper foil is, for example, 13 μm.
[0039] In one embodiment of the present invention, the negative electrode active layer includes a negative electrode active material, a conductive agent, a negative electrode binder, and a thickener. The negative electrode active material includes, for example, any one or more combinations of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, or lithium titanate. However, this application is not limited to these materials; other materials that can be used as battery negative electrode active materials may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0040] In one embodiment of the present invention, the negative electrode binder is selected from at least one of the following: polymerized styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylic acid (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), or carboxymethyl chitosan (CMCS). The thickener includes, for example, sodium carboxymethyl cellulose (CMC-Na), and the conductive agent is selected from any one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, or carbon nanofibers. The mass ratio of negative electrode active material, conductive agent, negative electrode binder and thickener in the negative electrode active layer is, for example, (94-97):(1-2):(1-2):(1-2).
[0041] In one embodiment of the present invention, the negative electrode active material is selected from natural graphite, the conductive agent is selected from conductive carbon black, the thickener is selected from sodium carboxymethyl cellulose, and the negative electrode binder is selected from styrene-butadiene rubber. In one embodiment of the present invention, the negative electrode active material, conductive agent, thickener, and negative electrode binder are mixed in a mass ratio of 96:1:1:2, deionized water is added, and the mixture is stirred evenly under vacuum to obtain a negative electrode slurry. The negative electrode slurry is coated onto copper foil, then air-dried at room temperature and transferred to an oven for drying. After cold pressing, edge trimming, cutting, and slitting, a negative electrode sheet is obtained. In other embodiments, the negative electrode sheet can also be obtained by any other method of forming a negative electrode sheet.
[0042] In one embodiment of the present invention, the electrolyte includes, for example, an organic solvent and a lithium salt. The organic solvent is selected from one or more of battery-grade ethylene carbonate (EC), propylene carbonate (PC), ethyl acetate (EA), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), or diethyl carbonate (DEC). The lithium salt is selected from one or more of lithium bis(fluorosulfonyl)imide (LiFSi), lithium difluorophosphate (LiPO2F2), lithium hexafluorophosphate (LiPF6), or lithium tetrafluoroborate (LiBF4). In one embodiment of the present invention, the lithium salt is selected from lithium hexafluorophosphate, and the organic solvent is selected from a mixture of ethylene carbonate, ethyl methyl carbonate, diethyl carbonate, and propylene carbonate. Ethylene carbonate, methyl ethyl carbonate, diethyl carbonate, and propylene carbonate are mixed, for example, in a volume ratio of 1:1:1:1. In an argon-atmosphere glove box with a water content of less than 10 ppm, thoroughly dried LiPF6 is dissolved in the mixed organic solvent and mixed evenly to obtain an electrolyte, wherein the concentration of LiPF6 is, for example, 1 mol / L.
[0043] In one embodiment of the present invention, a positive electrode, a separator, and a negative electrode are placed alternately, and a bare cell is obtained by stacking or winding. The bare cell is then installed in a square shell, baked to remove water, injected with electrolyte, and sealed. After further processing, including standing, hot and cold pressing, formation, clamping, and capacity testing, a finished lithium-ion battery is obtained. The designed capacity of the lithium-ion battery is, for example, 1000mAh.
[0044] The present invention will be explained in more detail below by referring to embodiments, which should not be construed as limiting. Appropriate modifications can be made within the scope of the present invention, and all such modifications fall within the technical scope of the present invention.
[0045] Example 1
[0046] Preparation of the diaphragm: A heat-resistant slurry with a total solute content of 36 wt% was prepared. In the heat-resistant slurry, the mass ratio of fumed alumina to nanofiber crystals was 2:8. The content of the first binder, acrylate, in the heat-resistant slurry was 5 wt%, and the content of the first dispersant, acrylic acid, in the heat-resistant slurry was 0.5 wt%. The nanocellulose had a diameter of 50 nm and a minimum length of 80 μm. The median particle size of the fumed alumina powder was 50 nm.
[0047] A polymer slurry with a total solute content of 10 wt% was prepared, wherein the mass ratio of the second binder polymethyl methacrylate, the third binder acrylic polymer, and the second dispersant octadecyl methacrylate was 89.542:9.75:0.708.
[0048] A heat-resistant slurry was coated onto a 10 μm thick polyethylene film with a porosity of 50% using a microgravure process. After drying, a heat-resistant layer with a thickness of 0.5 μm was formed. A polymer slurry was then sprayed onto the surface of the heat-resistant layer and dried to obtain a polymer layer. The mass-to-density ratio of the second dispersant to the second binder in each square meter of the polymer layer was 0.003, and the coating weight of the polymer layer was 0.5 g / m². 2 The coverage rate is 40%.
[0049] Preparation of positive electrode: LiNi 0.6 Co 0.2 Mn 0.2 O2, acetylene black, and polyvinylidene fluoride were mixed in a mass ratio of 97:1:2, and N-methylpyrrolidone solvent was added. The mixture was stirred until homogeneous and transparent to obtain a positive electrode slurry. The positive electrode slurry was uniformly coated onto aluminum foil, dried at room temperature, and then transferred to a vacuum drying oven for further drying. After cold pressing, edge trimming, cutting, and slitting, the positive electrode sheet was obtained.
[0050] Preparation of negative electrode sheet: Natural graphite, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber are mixed in a mass ratio of 96:1:1:2, deionized water is added, and the mixture is mixed evenly under the action of a vacuum stirrer to obtain a negative electrode slurry. The negative electrode slurry is coated on copper foil, and then dried at room temperature and transferred to an oven for drying. After cold pressing, edge trimming, sheet cutting and slitting processes, the negative electrode sheet is obtained.
[0051] Preparation of electrolyte: Ethylene carbonate, methyl ethyl carbonate, diethyl carbonate and propylene carbonate are mixed in a volume ratio of 1:1:1:1, for example. In an argon atmosphere glove box with a water content of less than 10 ppm, fully dried LiPF6 is dissolved in the mixed organic solvent and mixed evenly to obtain the electrolyte. The concentration of LiPF6 is, for example, 1 mol / L.
[0052] Battery fabrication: The positive electrode, separator, and negative electrode are stacked sequentially to obtain a bare cell, with the separator positioned between the positive and negative electrodes to provide insulation. The bare cell is then installed in a casing, baked to remove moisture, injected with electrolyte, and sealed. Following this, it undergoes a settling, hot-cold pressing, formation, clamping, and capacity testing process to obtain a finished lithium-ion battery with a capacity of 1000mAh.
[0053] In this invention, Examples 1-21 and Comparative Examples 1-2 are provided. The content of the second dispersant in the polymer layer, the coating amount of the polymer layer, the selection of the Dv50 of the fumed alumina, the diameter and length of the nanocellulose, and the mass ratio of fumed alumina to nanocellulose in Examples 1-21 and Comparative Examples 1-2 are adjusted. The variables in each example and comparative example are listed in Table 1. The ratio of the mass of the second dispersant per square meter to the density of the second binder is adjusted by adjusting the content of the second dispersant in the polymer slurry and the coating amount of the polymer layer. Different Dv50 particles are obtained by controlling the synthesis process of the fumed alumina or by customizing with the manufacturer. Different diameters and lengths of nanocellulose are obtained, for example, by customizing with the manufacturer. Except for the variables shown in Table 1, the remaining steps in Examples 1-21 and Comparative Examples 1-2 are the same as in Example 1.
[0054] In this invention, the lithium-ion batteries obtained in Examples 1-21 and Comparative Examples 1-2 were subjected to performance tests, and the test results are shown in Table 1.
[0055] In one embodiment of the present invention, a method for testing the coating amount of the polymer layer is as follows:
[0056] Using the diaphragms prepared in Examples 1-21 and Comparative Examples 1-2 as samples, the average thickness of the coating layer was first determined: after stacking ten layers of the diaphragm, the overall thickness T1 of the diaphragm was measured with a micrometer. After ion polishing of the diaphragm, cross-sectional analysis was performed, and the total thickness of the base film and heat-resistant layer in a single-layer diaphragm was measured as T2 using a scanning electron microscope (SEM). T1 / 10-T2 is the average thickness of the polymer layer. The coverage of the polymer layer was measured as S1 using a charge-coupled device (CCD) detector. The coating amount of the sample = (T1 / 10-T2)*S1*ρ', where ρ' is the total density of the polymer layer components / number of polymer types.
[0057] Alternatively, the separators obtained from the batteries fabricated in Examples 1-21 and Comparative Examples 1-2 can be disassembled. The resulting batteries, after cleaning and natural air drying, are used as samples. First, the average thickness of the coating layer is determined: after stacking ten layers of separator, the overall thickness T1 of the separator is measured using a micrometer. After ion polishing of the separator, a cross-sectional analysis is performed. The total thickness of the base film and heat-resistant layer in a single separator layer is measured using a scanning electron microscope as T2. T1 / 10 - T2 is the average thickness of the polymer layer. The coverage of the polymer layer is measured using a charge-coupled device (CCD) detector, and the coating amount of the sample is calculated as (T1 / 10 - T2) * S1 * ρ', where ρ' is the total density of the polymer layer components divided by the number of polymer types.
[0058] In one embodiment of the present invention, the method for testing the coverage of the polymer layer is as follows:
[0059] Based on the preparation process of the polymer layer obtained in Examples 1-21 and Comparative Examples 1-2, the coverage rate set when preparing the polymer layer in Examples 1-21 and Comparative Examples 1-2 was obtained;
[0060] Alternatively, take the diaphragms prepared in Examples 1-21 and Comparative Examples 1-2 as samples, use a three-dimensional digital microscope, place the diaphragm on the platform, align the microscope with the test position, set the magnification to 20x, set automatic area measurement, click next, take pictures, and the device will automatically generate the coverage value.
[0061] Alternatively, disassemble the batteries prepared in Examples 1-21 and Comparative Examples 1-2 to obtain the separator, use a three-dimensional digital microscope, place the separator on the platform, align the microscope with the test position, set the magnification to 20x, set automatic area measurement, click Next, take a picture, and the device will automatically generate a coverage value.
[0062] In one embodiment of the present invention, the method for testing material density is as follows:
[0063] The second adhesive used in Examples 1-21 and Comparative Examples 1-2 was used as a sample, and the material density data was obtained according to GB / T1033.1-2008;
[0064] In one embodiment of the present invention, the median particle size of fumed alumina is tested:
[0065] The fumed alumina used in the preparation process was taken as a sample, and the median particle size of the fumed alumina was obtained with reference to GB / T41949-2022.
[0066] Alternatively, the diaphragms prepared in Examples 1-21 and Comparative Examples 1-2 can be used as samples. Method 1: After calcining at 600℃ for 120h, fumed alumina can be obtained by filtration. The calcination and filtration can be repeated until the test requirements of GB / T41949-2022 are met. Method 2: The sample can be ultrasonically dissolved and shaken in NMP for 10h, washed and filtered to obtain fumed alumina. The ultrasonic dissolution and shaking can be repeated until the fumed alumina obtained by filtration meets the test requirements of GB / T41949-2022.
[0067] Alternatively, the separator can be obtained by disassembling the batteries prepared in Examples 1-21 and Comparative Examples 1-2, and then gaseous alumina can be obtained by method one or method two. The specific surface area and median particle size of the gaseous alumina can be obtained by testing.
[0068] In one embodiment of the present invention, the coating thickness is obtained, for example, by scanning electron microscopy.
[0069] In one embodiment of the present invention, the membrane impedance test is obtained by preparing the membranes obtained in Examples 1-21 and Comparative Examples 1-2 into Li-Li symmetric cells and then performing electrochemical impedance spectroscopy (EIS) tests.
[0070] In one embodiment of the present invention, the diameter and length of the nanocellulose used in the preparation process are obtained by testing with a transmission electron microscope, an atomic force microscope or a scanning electron microscope.
[0071] In one embodiment of the present invention, the polymer coating bonding force (BF) test is performed by hot pressing the diaphragm and the positive electrode sheet in a hot press at 95°C and 3 MPa for 60 seconds. The hot-pressed composite is then cut into 200mm*15mm strips, and three strips are tested separately. The lower end of the strip is opened, the electrode sheet is clamped in the lower clamp of the tensile testing machine, the diaphragm is pulled back and clamped in the upper clamp, the tensile testing machine is turned on, the tensile rate is 50mm / min, and the average bonding force of the three strips is read after the sample is peeled off.
[0072] In one embodiment of the present invention, the interface wrinkle performance test is carried out by disassembling the battery cell after it is fully charged, observing the wrinkle situation of the negative electrode sheet, and comparing it with the fully charged interface of the battery cell prepared in Comparative Example 1. The number of wrinkles on the electrode sheet to be tested is counted, and the reduction ratio of the number of wrinkles on the electrode sheet to be tested compared with the number of wrinkles on the electrode sheet of the battery cell prepared in Comparative Example 1 is calculated.
[0073] In one embodiment of the present invention, the lithium-ion battery cycle test is conducted at 25°C by subjecting the prepared lithium-ion battery to long-cycle charge-discharge, measuring its discharge capacity, and calculating its energy density. The battery test operates within a voltage range of 2.5V-4.3V, with a charge / discharge rate of 1C / 1C. The discharge capacity of the first cycle is recorded as the 1C discharge capacity. The test ends when the battery capacity reaches 80% of the first cycle capacity (80% State of Health, 80% SOH), and the number of cycles at room temperature is obtained.
[0074] In one embodiment of the present invention, the diaphragms obtained in Examples 1-21 and Comparative Examples 1-2 were used as samples, and the heat shrinkage rate of the diaphragms was obtained in accordance with GB / T36363-2018.
[0075] Alternatively, the separator can be obtained by disassembling the batteries prepared in Examples 1-21 and Comparative Examples 1-2, and the thermal shrinkage rate of the separator can be obtained in accordance with GB / T36363-2018.
[0076] In one embodiment of the present invention, the DCR improvement rate % test uses the DCR1 of a conventional diaphragm and the DCR2 of the diaphragm in this patent. The DCR improvement rate is (DCR1-DCR2) / DCR1.
[0077] DCR Test Method: Place the battery under test in an ambient temperature of 25±2℃. Then, apply a constant DC current I (usually 1.5C, where C is the battery's rated capacity) for 10 or 30 seconds. During this process, record the initial voltage U0 before the current is applied and the voltage U0 after the current is applied, and calculate the voltage change ΔU (ΔU=U0-U1). According to Ohm's law, calculate the DC internal resistance DCR=ΔU / I.
[0078] Table 1. Performance test results of the separator and lithium-ion battery in Examples 1-21 and Comparative Examples 1-2
[0079]
[0080] Please refer to Table 1. Comparing Examples 1-4 and Comparative Example 1, it can be seen that as the dispersant mass and the density ratio of the first binder increase, the membrane impedance increases, the battery cycle count first increases and then decreases, and the interfacial wrinkling performance improves. Therefore, controlling the dispersant mass and the density ratio of the first binder can reduce membrane impedance, improve battery cycle performance, and alleviate the interfacial wrinkling problem.
[0081] Please refer to Table 1. Comparing Examples 1 and 5-9, it can be seen that with the increase of fumed alumina content, within a set range, the membrane impedance is lower, the membrane thermal shrinkage rate is smaller, the interface wrinkling problem is improved, and the cycle performance of the lithium-ion battery is better. Therefore, by controlling the content of each substance in the heat-resistant layer, the heat resistance of the obtained membrane can be ensured, and the adhesion between the heat-resistant layer and the porous base film can be improved, thereby enhancing the interfacial compatibility between the heat-resistant layer and the porous base film.
[0082] Please refer to Table 1. Comparing Examples 1 and 10-12, it can be seen that as the median particle size of fumed alumina increases, the membrane impedance increases, while the membrane thermal shrinkage rate, cycle performance, and interfacial wrinkling performance remain at a high level. However, when the median particle size exceeds a set range, the performance of both the membrane and the battery decreases. Comparing Examples 1, 13-14, and 17, it can be seen that as the diameter of nanocellulose increases, the membrane impedance first decreases and then increases, while the cycle performance first increases and then decreases. Within the set range, the membrane exhibits better thermal shrinkage performance, greater adhesion, and fewer wrinkles. Comparing Examples 1, 15-17, it can be seen that as the length of nanocellulose increases, the membrane impedance first decreases and then increases, while the cycle performance first increases and then decreases. Within the set range, the membrane exhibits better thermal shrinkage performance, greater adhesion, and fewer wrinkles. Therefore, by adding nanocellulose and fumed alumina to form a network structure, the thermal stability and mechanical properties of lithium battery separators can be effectively improved. Furthermore, by controlling the size of nanocellulose and fumed alumina, the separator as a whole can have high adhesion, which can improve the cell interface wrinkling problem and thus improve the cycle performance of the battery.
[0083] Please refer to Table 1. Comparing Examples 1 and 18-21, it can be seen that as the amount of polymer coating increases, the polymer layer coverage increases, and the amount of polymer coating is 0.3 g / m². 2 -0.7g / m 2 When the polymer layer coverage is within the range of 25%-60%, the separator impedance remains low, the polymer coating adhesion increases with the increase of coating amount, the battery cycle count remains at a high level, and the interfacial wrinkle performance is improved. This is because if the coverage is too low, the overall adhesion of the separator is too low, the effect of cell hot-pressing composite is poor, and interfacial wrinkles will form, thus affecting the battery cycle performance. If the coverage is too high, the overall air permeability of the separator is too high, the overall impedance increases, and ultimately affects the battery cycle performance. Therefore, this application can obtain a low coating amount with a high polymer layer coverage, resulting in improved separator adhesion, improved interfacial wrinkle problem, reduced separator impedance, and improved long-cycle performance of the battery.
[0084] This invention also provides an electronic device comprising at least one of the aforementioned lithium-ion batteries, which provides electrical energy. The electronic device can be a vehicle, mobile phone, portable device, laptop computer, ship, spacecraft, electric toy, or power tool, etc. In one embodiment of this invention, the vehicle is, for example, a new energy vehicle, which can be a pure electric vehicle, a hybrid electric vehicle, or a range-extended electric vehicle, etc. Spacecraft include airplanes, rockets, space shuttles, and spacecraft, etc. Electric toys include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc. Power tools include metal cutting power tools, grinding power tools, assembly power tools, and railway power tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators, and electric planers, etc. The electronic device includes the aforementioned lithium-ion battery, and therefore the advantages of including the aforementioned lithium-ion battery are not elaborated here.
[0085] In summary, this invention proposes a separator and its application, which can improve the interfacial compatibility between the heat-resistant layer and the porous base film, improve separator impedance, obtain a smooth heat-resistant layer, thereby increasing the actual contact area between the heat-resistant layer and the polymer layer on it, improving the overall adhesion of the separator, improving the cell interface wrinkling problem, and thus improving the battery cycle performance. It can improve the uniformity of the formed polymer layer, obtaining a uniformly coated polymer layer. It can improve the mechanical properties of the separator while maintaining flexibility, improve the ion transport performance of the separator, reduce the contact area with the electrolyte, and improve the chemical stability of the separator. It can improve the high-temperature resistance of the separator, improve the thermal shrinkage of the porous base film at high temperatures, and ensure smooth lithium-ion conduction. By using a low coating amount and achieving a high polymer layer coverage, the resulting separator has improved adhesion, improved interface wrinkling problem, reduced separator impedance, and improved long-cycle performance of the battery.
[0086] The above description is merely a preferred embodiment of this application and an explanation of the technical principles employed. Those skilled in the art should understand that the scope of the invention involved in this application is not limited to the technical solutions formed by specific combinations of the above-described technical features. It should also cover other technical solutions formed by arbitrary combinations of the above-described technical features or their equivalents without departing from the inventive concept. For example, technical solutions formed by substituting the above-described features with (but not limited to) technical features with similar functions disclosed in this application. Except for the technical features described in the specification, the remaining technical features are known to those skilled in the art. To highlight the innovative features of this invention, the remaining technical features will not be described further here.
Claims
1. A diaphragm, characterized in that, At least including: Porous base membrane; A heat-resistant layer is disposed on at least one surface of the porous base membrane, the heat-resistant layer comprising fumed alumina and nanocellulose; as well as A polymer layer is disposed on the surface of the porous base membrane away from the heat-resistant layer and / or on the surface of the heat-resistant layer away from the porous base membrane, wherein the coating amount of the polymer layer is 0.3 g / m². 2 -0.7g / m 2 The polymer layer has a coverage of 25%-60%.
2. The diaphragm according to claim 1, characterized in that, In the heat-resistant layer, the mass ratio of the fumed alumina to the nanocellulose is 2:8-5:5, and the median particle size of the fumed alumina powder is 50nm-100nm.
3. The diaphragm according to claim 1, characterized in that, The nanocellulose includes at least one of cellulose nanofibers or nanofiber crystals, and the diameter of the nanocellulose is less than or equal to 100 nm, and the length of the nanocellulose is less than or equal to 100 μm.
4. The diaphragm according to claim 1, characterized in that, The heat-resistant layer further includes a first dispersant and a first binder, wherein the first dispersant is selected from acrylic dispersants and the first binder is selected from acrylate binders.
5. The diaphragm according to claim 1, characterized in that, The heat-resistant layer has a thickness of 0.2 μm-0.9 μm and a bulk density of 0.5 g / cm³. 3 -1.2g / cm 3 The diaphragm has a heat shrinkage rate of less than 1% after being baked at 150°C for 1 hour.
6. The diaphragm according to claim 1, characterized in that, The polymer layer includes a second dispersant and a second binder. The mass ratio of the second dispersant to the material density of the second binder per square meter of the polymer layer is 0.002-0.005:1, and the material density of the second binder is 0.6 g / cm³. 3 -1.2g / cm 3 .
7. The diaphragm according to claim 6, characterized in that, The second binder comprises at least one of polymethyl methacrylate and its copolymers or polyacrylate and its copolymers; the second dispersant comprises octadecyl methacrylate.
8. The diaphragm according to claim 6, characterized in that, The polymer layer further includes a third binder, which includes at least one of polyacrylate and its copolymers, polyacrylonitrile or acrylic polymer, and the molecular weight of the third binder is greater than 300,000.
9. The diaphragm according to claim 8, characterized in that, In the polymer layer, the mass ratio of the second binder to the second dispersant is 75-400:1, the mass ratio of the second binder to the third binder is 8-15:1, the median particle size of the second binder is 5μm-10μm, and the median particle size of the third binder is less than 1μm.
10. A lithium-ion battery, characterized in that, Includes the diaphragm as described in any one of claims 1-9.